Interpreting Grief as A Child’s Life Experience: Children’s Film Analysis - Buntoro, Ruth Shieren; Trihastutie, Nopita - (Universitas Teknokrat Indonesia, 2024)
This study aims to examine how the process of growing in grief affects the personality of the main character in “When Marnie Was There” film. This study employed a descriptive interpretive method to get a descriptive exposure in writing from the film. The findings show that “When Marnie Was There” film depicts a child who is experiencing feelings of alienation and disconnection. A variety of emotions, such as grief, are real-life experiences that are portrayed in the dialogue between the characters and in incidental events. This life experience is mirrored in the four stages of the multifaceted grieving process. In conclusion, as the main character passes through the four stages of personal growth and healing—which are represented in the scenes and utterances—and experiences a spectrum of emotions, the main character’s journey demonstrates the complexity and multi-dimensional of grief. “When Marnie Was There” film offers a moving examination of identity, loss, and the role that acceptance and friendship may have in a child’s grieving process.